Counterproductive Work Behavior: The Role of Work Life Balance And Job Stress - Devita Maharani; Dewi Khrisna Sawitri (Dinasti International Journal of Education Management And Social Science, 2025)
The present investigation seeks to determine the impact of Work Life Balance and Job Stress on Counterproductive Work Behavior in an outsourcing company, focusing on security personnel as the research object. The research methodology employed a quantitative approach utilizing a saturated sampling procedure, encompassing 96 security personnel as study participants. Statistical analysis was conducted via Partial Least Squares (PLS) structural equation modeling. The empirical findings demonstrate that Work Life Balance has a negative and significant effect on Counterproductive Work Behavior, while Job Stress has a positive and significant effect on Counterproductive Work Behavior. This means that a balanced personal and professional life can reduce the emergence of deviant behaviors, whereas unmanaged stress increases the risk of counterproductive actions. These findings provide a foundation for management to design more effective work systems and psychological support strategies to minimize deviant behavior in the workplace.